2016 Joint Rail Conference 2016
DOI: 10.1115/jrc2016-5793
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Design Rail Cant on Concrete Crosstie Rail Seat Pressure Distribution

Abstract: Previous research has focused on the effect of rail cant on rail wear and wheel/rail interaction, indicating that a steeper rail cant results in increased wear on rails and wheels. However, no research has investigated the effect of rail cant on the crosstie rail seat pressure distribution. Past research at the University of Illinois at Urbana-Champaign (UIUC) looked into the effect of negative (reverse) rail cant on pressure distribution across the rail seat utilizing matrix-based tactile surface sensors (MBT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
(6 reference statements)
0
0
0
Order By: Relevance
“…The investigation of Wu et al [22] indicated that the reverse rail cant can increases the risk of a rail rollover derailment. Ghosh et al [23] studied the effect of rail cant on the stress distribution of a concrete sleeper using the method of static test. The results from the parametric study of Mojumder et al [24] indicate that the effects of the rail cant angle and rail stiffness were not high enough for crack initiation.…”
Section: Introductionmentioning
confidence: 99%
“…The investigation of Wu et al [22] indicated that the reverse rail cant can increases the risk of a rail rollover derailment. Ghosh et al [23] studied the effect of rail cant on the stress distribution of a concrete sleeper using the method of static test. The results from the parametric study of Mojumder et al [24] indicate that the effects of the rail cant angle and rail stiffness were not high enough for crack initiation.…”
Section: Introductionmentioning
confidence: 99%